Generic Model of a Satellite Attitude Control System - Janusz Narkiewicz; Mateusz Sochacki; Bartłomiej Zakrzewski (International Journal of Aerospace Engineering)
A generic model of a nanosatellite attitude control and stabilization system was developed on the basis of magnetorquers and reaction wheels, which are controlled by PID controllers with selectable gains. This approach allows using the same architectures of control algorithms (and software) for several satellites and adjusting them to a particular mission by parameter variation. The approach is illustrated by controlling a satellite attitude in three modes of operation: detumbling after separation from the launcher, nominal operation when the satellite attitude is subjected to small or moderate disturbances, and momentum unloading after any reaction wheel saturation. The generic control algorithms adjusted to each mode of operation were implemented in a complete attitude control system. The control system model was embedded into a comprehensive simulation model of satellite flight. The simulation results proved the efficiency of the proposed approach.